Entry Threats and Pricing in the Generic Drug Industry - Tenn, Steven; Wendling, Brett W (The Review of Economics and Statistics, 2014)
We use the unique regulatory environment of the pharmaceutical industry to examine how potential competition affects generic drug pricing. Our identification strategy exploits a provision of the Hatch-Waxman Act that awards 180 days of marketing exclusivity to the first valid generic drug applicant against the holder of a branded drug patent. In smaller drug markets, we find that price falls in response to an increase in potential competition. We also find that few manufacturers enter these markets, indicating this price reduction is an effective deterrent. In contrast, we find that generic incumbents accommodate entry in larger drug markets.